2003
DOI: 10.1002/pssc.200303129
|View full text |Cite
|
Sign up to set email alerts
|

Indium distribution in epitaxially grown InGaN layers analyzed by transmission electron microscopy

Abstract: An overview is given about microstructure and composition analyses of InGaN quantum wells embedded in Ga(Al)N barriers to study the mechanisms which determine the In distribution in epitaxially grown InGaN layers. The applied technique is transmission electron microscopy (TEM). The main prerequisite for this work was the development of a technique based on high-resolution lattice fringe images that allows quantitative chemical analyses of InGaN on an atomic scale. A large variety of samples was investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
(41 reference statements)
5
34
1
Order By: Relevance
“…In the light of the Smeeton et al [16,17] papers, which suggested that the gross indium-rich clusters in InGaN quantum wells reported by many researchers might be due to electron beam damage, the Gerthsen group revised their earlier conclusions [11,12]. They observed that the indium concentration in the clusters increased with increasing irradiation time in the electron microscope.…”
Section: Does Tem Give Any Evidence For Genuine In Clustering?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of the Smeeton et al [16,17] papers, which suggested that the gross indium-rich clusters in InGaN quantum wells reported by many researchers might be due to electron beam damage, the Gerthsen group revised their earlier conclusions [11,12]. They observed that the indium concentration in the clusters increased with increasing irradiation time in the electron microscope.…”
Section: Does Tem Give Any Evidence For Genuine In Clustering?mentioning
confidence: 99%
“…By using Vegard's law, the lattice parameter map can be converted to a composition map. For InGaN quantum wells grown with 10-20% indium, the indium-rich clusters are typically found to contain at least 80% indium [10][11][12][13], although the projection problem in TEM makes it difficult to quantify the indium content. We will call such clusters "gross indium-rich clusters".…”
Section: The Evidence From Electron Microscopy For Indium-rich Clustersmentioning
confidence: 99%
“…The details of the procedure are outlined in Ref. [10]. Optimized imaging conditions for the formation of lattice-fringe images were obtained by tilting the sample by about 5 from the /1 0 % 1 0S or /1 1 % 2 0S zone-axis orientation to excite only {0 0 0 2n} beams.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The characterization of the QWs was carried out by (HR)TEM. Local and average In concentrations were obtained on an atomic scale based on HRTEM images using the digital analysis of lattice images (DALI) evaluation method [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The interference of only two beams leads to fringe images which are obtained in our case by a two-beam excitation condition with strongly excited (0000) and (0002) beams. It can be shown by image simulations that artifacts due to variations of the sample thickness and objective lens defocus ∆f are negligible if the (0002) beam is centered on the optic axis and if only the (0000) and (0002) beams are transmitted through the objective aperture [10]. The apparent loss of resolution along the (0002) fringes compared to a conventional zone-axis image does not present a problem because only the distances between the (0002) fringes need to be measured.…”
Section: Methodsmentioning
confidence: 99%